Ascending aortic dilation in adult patients with congenital ventricular septal defect: An observational study. Issue 15 (April 2018) - Li, Hai-Yang; Zhao, Yuan-Fei; Dai, Lu; Xu, Shi-Jun; Zhang, Hong-Jia; Jiang, Wen-Jian
Abstract : Abstract: Many adult patients with congenital ventricular septal defect (VSD) also developed ascending aortic dilation, but few report the clinical features and surgical management of these patients. This study was designed to study ascending aortic dilation in adult patients with congenital VSD, and summarized the treatment experience and prognosis. To assess the clinical features and surgical management, we performed a retrospective analysis on preoperative data, intraoperative data, and postoperative data from the adult patients with congenital VSD who developed ascending aortic dilation in our institution from February 2010 to December 2016. From February 2010 to December 2016, we operated on 13 adult patients (12 males, 92.31%) with VSD who developed ascending aortic dilation. Median age was 37 (interquartile range 14) years. All patients suffered from perimembranous VSD and received surgical treatment. Their symptoms were all improved after surgery, no deaths occurred. Surgery is feasible for the ascending aortic dilation in adult patients with congenital VSD. Both proper perioperative treatment and close monitoring are required for the successful surgery.